KEBIJAKAN PEMERINTAH TENTANG MEREK DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP UMKM - Belardo Prasetya Mega Jaya; Mohamad Fasyehhudin; Wardatun Naddifah (Jurnal Ilmiah Advokasi, 2022)
Micro, Small Medium Enterpise (MSMEs) play a vital part in a financial improvement in Indonesia. In setting up a business, very much like other enormous ventures, MSMEs won’t ver escape from Licensed innovation Privilages, particularly reserve. This brand name enlistment will stay away from counterfeiting and get lawfull assurance from the public authority. However, truth the told there are as yet numerous MSMEs that poor person enrolled their brand names since they are compelled by capital and comprehension of the advantages of the brand name. Considering this, a guideline is expected to secure the brands possessed by the MSME business. So in this review, I will analyze how government strategies give lawfull insurance to MSMEs. This examination utilizes standardizing juridicial exploration strategies. The consequence of the review show that the Public authority’s strategy in giving lawful insurance to MSMEs is to give accommodation in brand name enlistment, in particular the enrollment expense for MSMEs brands which is less expensive than non-UMKM brands, teaming up with the Chief General of Data ad Correpodence Innovation of the Service of Cooperatives and MSMEs, escalated awards for financing the enlistment of MSME marks, and can complete aggregate brand name enrollmens for MSME business.      Keywords : Legal Protection, Government Policy, MSMEs, Law Number 20 year 2016 on Merk                   and IG